2019
DOI: 10.1093/carcin/bgz045
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling UCA1 lncRNA prognostic utility in urothelial bladder cancer

Abstract: In the era of precision oncology, bladder cancer (BlCa) is characterized by generic patient management and lack of personalized prognosis and surveillance. Herein, we have studied the clinical significance of urothelial cancer associated 1 (UCA1) lncRNA in improving patients’ risk stratification and prognosis. A screening cohort of 176 BlCa patients was used for UCA1 quantification. The Hedegaard et al. (n = 476) and The Cancer Genome Atlas (TCGA) provisional (n = 413) were analyzed as validation cohorts for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…In the bladder cancer studies, various dysregulated lncRNAs have been identified in both bladder cancer tissues and cells. For examples, Avgeris et al [10] screened a cohort of 176 bladder cancer patients, and identified lncRNA urothelial cancer associated 1 (UCA1) as a superior prognostic factor of disease early-relapse and progression in the bladder cancer patients. Liu et al [11] revealed that lncRNA neuroblastoma-associated transcript 1 exerted the tumor-suppressive effects on the malignant bladder cancer cells via regulating miR-21/suppressor of cytokine signaling 6 axis.…”
Section: Introductionmentioning
confidence: 99%
“…In the bladder cancer studies, various dysregulated lncRNAs have been identified in both bladder cancer tissues and cells. For examples, Avgeris et al [10] screened a cohort of 176 bladder cancer patients, and identified lncRNA urothelial cancer associated 1 (UCA1) as a superior prognostic factor of disease early-relapse and progression in the bladder cancer patients. Liu et al [11] revealed that lncRNA neuroblastoma-associated transcript 1 exerted the tumor-suppressive effects on the malignant bladder cancer cells via regulating miR-21/suppressor of cytokine signaling 6 axis.…”
Section: Introductionmentioning
confidence: 99%
“…The differential expression of lncRNA in malignant tumors and the molecular mechanism of action have been gradually investigated, and more and more lncRNAs have been found to be closely related to the occurrence and development of tumors. Some lncRNAs, such as ITGB1, UCA1, and DUXAP10, have been reported to play a key role in bladder cancer, significantly affecting the proliferation, migration, invasion, drug resistance, and other malignant biological behaviors of bladder cancer cells, and are correlated with early diagnosis, recurrence, metastasis, and prognosis of bladder cancer (Lv et al, 2018;Avgeris et al, 2019;Dai et al, 2019). LINC00511 is a newly discovered lncRNA with an oncogenic function, which can promote the proliferation and invasion of tumor cells by regulating miRNA expression (Wu et al, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using GENCODE annotations would only examine 19,812 transcripts, compared to the 107,039 transcripts in LNCipedia [10]. Previous studies have identified that lncRNAs like LINC00460, UCA1, LINC00958, LINC01296, SNH12, and DUXAP8 are implicated in bladder cancer, but did not examine the entire landscape of lncRNA transcripts [11,18,20,21].…”
Section: Discussionmentioning
confidence: 99%